1987
DOI: 10.1590/s0074-02761987000300012
|View full text |Cite
|
Sign up to set email alerts
|

Estudo pareado da cardiopatia chagásica no Rio Grande do Sul, Brasil: comportamento das alterações eletrocardiográficas em função da cor

Abstract: The pattern of ECG changes of 150 black individuals from rural areas of southern Rio Grande do Sul, Brazil, was compared with that of a group of 150 whites of similar age, sex and geographical residence. The mean age of the study group was 39.2 years (9-78 years), and 62% were women. 84 out of the 150 showed positive serological reactions to infection by Trypanosoma cruzi. The prevalence of ECG changes was significantly higher among the blacks, irrespective of their serological state. Those changes which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The existence of an association is plausible for at least two reasons: first, familial aggregation of T . cruzi seropositivity and ECG abnormalities have been found in highly endemic areas, suggesting that genetic variation may play a role in susceptibility to infection as well as disease progression [ 9 , 10 ]; second, an earlier publication, using ethnoracial self-classification, reported greater prevalence of ECG abnormalities among Black middle-aged adults relative to their White counterparts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of an association is plausible for at least two reasons: first, familial aggregation of T . cruzi seropositivity and ECG abnormalities have been found in highly endemic areas, suggesting that genetic variation may play a role in susceptibility to infection as well as disease progression [ 9 , 10 ]; second, an earlier publication, using ethnoracial self-classification, reported greater prevalence of ECG abnormalities among Black middle-aged adults relative to their White counterparts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them are male gender (Zicker 1990, Pereira-Barretto et al 1993, age (Zicker 1990), physical strain (Zicker 1990), exposure to reinfection (Macedo 1973), black skin color (Baruffa et al 1987), and family history of cardiovascular disease (Zicker 1990, Gontijo et al 1996. Most of these studies are cross-sectional, and the most adequate approach to investigate causative factors is either case-control or cohort-based.…”
Section: Discussionmentioning
confidence: 99%
“…Baruffa et al (1987) analyzed the pattern of ECG changes in 150 black individuals from rural areas of southern Brazil, and compared them to those of 150 whites of similar age and gender distribution living in the same area. The mean age of their study group was 39.2 years (9-78 years), and 62% were women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To know the seroprevalence of T. cruzi in this population is essential since studies carried out in Afro-descendant communities in other countries, such as Brazil, have reported contradictory results. Some authors have suggested that infected Afro-descendants, particularly those over 80 years old, have a greater probability of developing severe electrocardiographic abnormalities associated with CD and propensity to die [ 10 , 11 ]. At the same time, other studies indicate that some communities where Afro-descendants know the vector and have reported contact with it have little seropositivity to T. cruzi [ 12 ].…”
Section: Introductionmentioning
confidence: 99%